Harmonizing Corporate Reporting: A Narrative Review on ESG, IR, and Global Investor Perceptions - Yosepha, Sri Yanthy (Yayasan Sinergi Kawula Muda, 2025)
The growing importance of non-financial disclosure in enhancing corporate transparency and investor trust has led to significant interest in ESG and Integrated Reporting (IR) frameworks. This narrative review aims to evaluate the extent to which ESG reporting, IR, stakeholder engagement, and global reporting standards impact the value relevance of corporate disclosures. Literature was sourced from Scopus, Web of Science, and Google Scholar, using systematic keyword combinations and inclusion criteria focused on peer-reviewed studies related to financial reporting, value relevance, and investor decision-making. Findings confirm that ESG and IR significantly increase investor confi dence by reducing information asymmetry, providing a more holistic understanding of corporate performance, and aligning long-term sustainability with financial outcomes. Stakeholder engagement and the use of global standards like IFRS and GRI further support consistency and comparability of disclosures across regions. However, challenges such as regulatory fragmentation, varying industry practices, and disparities in technological capacity hinder universal adoption. The study highlights the necessity for regulatory harmonization, increased financial literacy, and digital transformation as critical enablers for effective value communication. It calls for future research to deepen understanding of sectoral variations and technological integration in ESG monitoring. The review ultimately emphasizes the need for inclusive, standardized, and transparent reporting to strengthen global investor confidence and sustainable economic growth.